A Deadly Path: Bacterial Spread During Bubonic Plague. Issue 4 (April 2016) - Gonzalez, Rodrigo J.; Miller, Virginia L.
Abstract : Yersinia pestis causes bubonic plague, a fulminant disease where host immune responses are abrogated. Recently developed in vivo models of plague have resulted in new ideas regarding bacterial spread in the body. Deciphering bacterial spread is key to understanding Y. pestis and the immune responses it encounters during infection.